2020
DOI: 10.2337/dc19-1310
|View full text |Cite|
|
Sign up to set email alerts
|

Randomized Controlled Trial of Mobile Closed-Loop Control

Abstract: Assess the efficacy of inControl AP, a mobile closed-loop control (CLC) system. RESEARCH DESIGN AND METHODSThis protocol, NCT02985866, is a 3-month parallel-group, multicenter, randomized unblinded trial designed to compare mobile CLC with sensor-augmented pump (SAP) therapy. Eligibility criteria were type 1 diabetes for at least 1 year, use of insulin pumps for at least 6 months, age ‡14 years, and baseline HbA 1c <10.5% (91 mmol/mol). The study was designed to assess two coprimary outcomes: superiority of CL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 22 publications
1
24
0
Order By: Relevance
“…At present, there are two commercially‐available AID systems in the US: the first system (Medtronic 670G, Medtronic, Ireland) was initially approved for ages 14 years and older and was subsequently lowered to ages 7 years 1 ; and the most recent system (Tandem Control‐IQ, Tandem Diabetes Care, San Diego CA) was also originally approved for use in 14 years of age or older 2 and later lowered to 6 years. Despite this growing availability, there are few clinical trials on the use and efficacy of these AID systems in younger children; this population is especially vulnerable to problems with glucose control such as increased glucose variability and episodes of severe hypoglycemia and therefore may benefit from AID technology 3‐7 …”
Section: Introductionmentioning
confidence: 99%
“…At present, there are two commercially‐available AID systems in the US: the first system (Medtronic 670G, Medtronic, Ireland) was initially approved for ages 14 years and older and was subsequently lowered to ages 7 years 1 ; and the most recent system (Tandem Control‐IQ, Tandem Diabetes Care, San Diego CA) was also originally approved for use in 14 years of age or older 2 and later lowered to 6 years. Despite this growing availability, there are few clinical trials on the use and efficacy of these AID systems in younger children; this population is especially vulnerable to problems with glucose control such as increased glucose variability and episodes of severe hypoglycemia and therefore may benefit from AID technology 3‐7 …”
Section: Introductionmentioning
confidence: 99%
“…Several randomized trials tested dosing algorithms for automated insulin delivery systems, comparing its efficacy to sensor-augmented pump therapy, in outpatient unsupervised settings with no remote monitoring. [7][8][9][10][11][12]14 Here, we present a relatively short study over 12 days that assesses our dosing algorithm in outpatient unsupervised settings. The algorithm was a less aggressive version than our previous algorithm, [18][19][20] to emphasize safety in our first outpatient study.…”
Section: Discussionmentioning
confidence: 99%
“…The Cambridge algorithm was tested in several trials, [7][8][9] including in participants with suboptimal 8 and good glycemic control, 9 and consistently showed improvements in glucose control. The University of Virginia's algorithm was also tested in several clinical trials, [10][11][12] and showed improvements in glucose control, although the benefits were lower when the algorithm was embedded in a phone as opposed to a pump. 11,12 The Medtronic first-generation dosing algorithm was tested in several nonrandomized trials, 13 but their second-generation algorithm was recently tested in a 4-week randomized trial, 14 and also showed improvements in glucose control.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies, using a variety of systems with varying algorithms, pump, and sensors, have been performed in adults and children (163)(164)(165)(166)(167)(168)(169)(170)(171)(172)(173). Evidence suggests such systems may reduce A1C levels and improve time in range (174)(175)(176)(177)(178). They may lower the risk of exerciserelated hypoglycemia (179) and may have psychosocial benefits (180)(181)(182)(183).…”
Section: Insulin Pumps In Patients With Type 2 and Other Types Of Diamentioning
confidence: 99%